In silico analyses of missense mutations in coagulation factor VIII: identification of severity determinants of haemophilia A. (9th April 2015) - Sengupta, M.; Sarkar, D.; Ganguly, K.; Sengupta, D.; Bhaskar, S.; Ray, K.
Summary Factor VIII (FVIII) mutations cause haemophilia A (HA), an X‐linked recessive coagulation disorder. Over 1000 missense mutations in FVIII are known and they lead to variable clinical phenotypes (severe, moderate and mild). The exact molecular basis of this phenotypic heterogeneity by FVIII missense mutations is elusive to date. In this study, we aimed to identify the severity determinants that cause phenotypic heterogeneity of HA. We compiled and curated a data set of 766 missense mutations from the repertoire of missense mutations in FVIII. We analysed these mutations by computational programs (e.g. Swiss‐PdbViewer) and different mutation analysis servers (e.g. SIFT, PROVEAN, CUPSAT, PolyPhen2, MutPred); and various sequence‐ and structure‐based parameters were assessed for any significant distribution bias among different HA phenotypes. Our analyses suggest that 'mutations in evolutionary conserved residues', 'mutations in buried residues', mutation‐induced 'steric clash' and 'surface electrostatic potential alteration' act as risk factors towards severe HA. We have developed a grading system for FVIII mutations combining the severity determinants, and the grading pattern correlates with HA phenotype. This study will help to correctly associate the HA phenotype with a mutation and aid early characterization of novel variants.